STRENGTHEN THE ROLE OF MUNĀSABAH IN INTERPRETING THE AL-QUR’AN: STUDY OF M. QURAISH SHIHAB PERSPECTIVE ON TAFSIR AL-MISHBAH - Fatih, M. (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2021)
The verses of the Qur’an correspond to each other so that between one part and another explain to one another (al-Qur’ān yufassiru ba’d}uhu ba’d}ā). One of Ulūm al-Qur’ān that examines the reasons and rationality of the sequence and order of parts of the Qur’an is the Munāsabah, that will guide Mufassir in interconnections between parts of the Qur’an. M. Quraish Shihab in his book, Tafsir al-Mishbah, is the only interpretation of the Qur’an 30 juz in Indonesia that consistently applies its approach to the study of the Qur’an in its various forms, as the title of the work implies. This article aims to cover out the role of Munāsabah in Tafsir al-Mishbah. This article is a literal study by making Tafsir al-Mishbah as a major data source. By descriptive and analysis method, finally, this article comes to the conclusion that the role of munāsabah in the al-Misbah has 5 roles; first, prevent the interpreter from misinterpretation; second, removes the obscurity between the multiple choice of meanings and leads to the corresponding meaning; third, presents a product of in-depth and detailed interpretation; fourth, assist the interpreter in uncovering the secret behind the redaction of the verse; fifth, helps the interpreter to conclude Islamic Jurisprudens on the ayat al-ah}kām